1987
DOI: 10.1093/jac/20.suppl_b.69
|View full text |Cite
|
Sign up to set email alerts
|

Activity of roxithromycin against Toxoplasma gondii in murine models

Abstract: Investigations into the activity of roxithromycin against murine toxoplasma infections are reviewed. Roxithromycin is an active drug against murine toxoplasmosis after intraperitoneal challenge with the RH strain of Toxoplasma gondii. Roxithromycin protected 100% of mice after five daily doses of 540 mg per kg administered by gavage. The cure rate after treatment of peritoneal infections seemed to be related to the length of the therapy. Roxithromycin also decreased the number of toxoplasma cysts, after intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This figure confirms the clinical inefficacy of pentamidine in the prevention of toxoplasmosis, and should be viewed in the context of the rate of onset of cerebral toxoplasmosis in HIVpositive patients, which at present in France is estimated at 15.3% [14]. In contrast, there are extensive data [1][2][3][4][5]13] on the antitoxoplasma activity of roxithromycin, both in vitro and in vivo in animals. These reflect the parasitostatic and sometimes parasiticidal action of the drug on T. gondii.…”
Section: Cerebral Toxoplasmosissupporting
confidence: 53%
See 1 more Smart Citation
“…This figure confirms the clinical inefficacy of pentamidine in the prevention of toxoplasmosis, and should be viewed in the context of the rate of onset of cerebral toxoplasmosis in HIVpositive patients, which at present in France is estimated at 15.3% [14]. In contrast, there are extensive data [1][2][3][4][5]13] on the antitoxoplasma activity of roxithromycin, both in vitro and in vivo in animals. These reflect the parasitostatic and sometimes parasiticidal action of the drug on T. gondii.…”
Section: Cerebral Toxoplasmosissupporting
confidence: 53%
“…In a pilot study in 1989 on the prevention of PCP and cerebral toxoplasmosis, we compared roxithromycin with pentamidine aerosols. Roxithromycin, an ether oxime derivative of erythromycin, was chosen on the basis of in vitro and in vivo efficacy in animal studies with Toxoplasma gondii infection [1][2][3][4][5] and of the clinical efficacy against PCP in patients intolerant of trimethoprim/sulphamethoxazole (TMP/SMX) and of pentamidine [6]. The pharmacokinetic properties of roxithromycin, namely high serum cerebral tissue concentrations [7], long half-life [8], and good tolerance [9] also favoured this choice.…”
Section: Introductionmentioning
confidence: 99%
“…1990). Utilizing a mouse model for toxoplasmic encephalitis, Hofflin and Remington (1987b) and Chang and Pechere (1987) found that roxithromycin and interferon act synergistically to delay death against cerebral toxoplasmosis; similarly, azithromycin acts synergistically with interferon against murine cerebral toxoplasmosis (Araujo et al 1988). Pyrimethamine-clindamycin mixtures have been used to treat human cerebral toxoplasmosis in AIDS patients.…”
Section: Treatment Of T Gondii Infectionsmentioning
confidence: 99%